Effect of copper on some biochemical parameters in lambs - İsmail Şen; Ercan Keskin; Mahmut Ok; Hüdai İpek; Ramazan Çöl (Eurasian Journal of Veterinary Sciences)
Experimentally induced sub-clinical coppeı deficiency and copper added to a ration were evaluated to find out how some biochemical parameters ol Akkaraman lambs were affected m this study. This study was performed on total of 18 healthy lambs, aging 3 months and weighing between 16-18 kg Animals were divided into three groups according to the body weight as group 1 (control), group It (copper added) and group III (copper deficiency). Blood samples were collected before the experiment and at the end ol three monlhs. No clinical symptoms were observed related lo copper toxicity or delraency In the groups II and III. respectively. Although biochemical parameters ol lambs in groups II and III showed individual differences compared to the controls, they were not statstically significant. As a result, it was determined that experimentally induced sub-clinic copper dificiency and 25 mg/kg copper added to a ration had no important effects in the some biochemical parameters.